CUSTOMER SATISFACTION AT RR CAFE DELIMA PEKANBARU INFLUENCED BY FACILITIES AND MENU VARIATIONS - Librina Tria Putri; Yulizar Baharuddin, Muhammad Nasir (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to determine the influence of facilities and menu variants oncustomer satisfactionat RR Cafe Delima Pekanbaru. The analysis used in this research was multiple linear analysis with a total of 99 respondents. Hypothesis testing is carried out by simultaneous testing and partial testing. Based on the research results, it can be concluded that the facilities and menu variants simultaneously affectcustomer satisfaction. So arepartially the facilities and menu variants have an influence oncustomer satisfactionat RR Cafe Delima Pekanbaru. Facilities and menu variants have a very strong relationship with customer satisfaction with a contribution of 65.90%. Meanwhile, the remaining 34.10% is determined by other variables not included in this research.